Semiconductor graphite material and preparation method thereof
Through specific raw material ratios and optimized calcination conditions, the preparation process of semiconductor graphite materials is simplified, the existing process complex and cost problems are solved, and high-performance semiconductor graphite materials are obtained.
Patent Information
- Application Number
- CN202411733527.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The preparation process of existing semiconductor graphite materials is complex, requiring impregnation and secondary carbonization, resulting in high production costs.
Using specific raw material ratios and optimized calcination conditions, high-performance semiconductor graphite materials can be prepared through one calcination and graphitization treatment, simplifying the process flow.
The obtained semiconductor graphite material has high flexural strength, compressive strength, hardness and density, and has low resistivity, low porosity and ash content, reducing production costs.
Smart Images

Figure BDA0005160908800000051 
Figure BDA0005160908800000071 
Figure BDA0005160908800000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor graphite materials, and in particular relates to a semiconductor graphite material and a preparation method thereof. Background Art
[0002] Semiconductor materials are widely used in the modern electronics industry, including integrated circuits, solar cells, sensors, and optoelectronic devices. As a typical carbon-based material, graphite has excellent electrical conductivity, thermal conductivity, and mechanical properties. Its application in the semiconductor field has gradually increased in recent years.
[0003] In the prior art, a Chinese patent with publication number CN 117534467 A discloses a method for preparing a highly homogeneous special graphite material for an epitaxial growth substrate, wherein the main raw materials are needle-shaped petroleum coke, needle-shaped asphalt coke, modified artificial graphite, and modified asphalt; the mass ratio of the needle-shaped petroleum coke, needle-shaped asphalt coke, and modified artificial graphite is 5:4:1-8:1:1; while maintaining various indicators of the graphite itself, the technical solution can also effectively enhance special single indicators. However, the preparation method of the technical solution requires impregnation treatment and secondary carbonization treatment, and the process is complicated.
[0004] Lv Zunhua and Zhang Junhua published a study on special graphite for semiconductor matrix in the journal Carbon Technology, which disclosed the use of raw material processing technology to coat the pitch coke for heat treatment and then spheroidize the particles. The results showed that after the raw materials were processed, the strength, thermodynamic properties, electrical properties, isotropy, etc. of the test products were greatly improved; however, the technical solution did not disclose its roasting process. Summary of the invention
[0005] In view of the above problems, the present invention provides a semiconductor graphite material and a preparation method thereof. The semiconductor graphite material of the present invention has higher flexural strength, compressive strength, hardness and density; lower resistivity, porosity and ash content; and the preparation process is simpler, thereby reducing production costs.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The invention provides a semiconductor graphite material. The raw materials include 23-33% of asphalt coke powder, 23-33% of raw petroleum coke powder, 5-15% of artificial graphite powder, 3-8% of natural graphite powder, and the balance is modified asphalt in percentage by mass.
[0008] In some preferred embodiments, the mass ratio of the asphalt coke powder, the raw petroleum coke powder, the artificial graphite powder and the natural graphite powder is 4-7:4-7:1.6-2:1.
[0009] In a preferred embodiment, the semiconductor graphite material comprises, by mass percentage, 28% asphalt coke powder, 28% raw petroleum coke powder, 9% artificial graphite powder, 5% natural graphite powder, and the remainder is modified asphalt.
[0010] In a preferred embodiment, the particle size of the asphalt coke powder: the sieve particle size -320# is 80-90%.
[0011] In the present invention, the sieve particle size -320# represents the powder content with a sieve particle size below the 320-mesh sieve.
[0012] In some preferred embodiments, the average particle size D50 of the raw petroleum coke powder is 10-20 μm.
[0013] In some preferred embodiments, the particle size of the artificial graphite powder: sieve particle size -320# is 80-90%.
[0014] In some preferred embodiments, the particle size of the natural graphite powder: sieve particle size -320# is 80-90%, pH=7.
[0015] Preferably, the natural graphite powder is T395 graphite powder produced by Qingdao Nanshu Ruiying Graphite Co., Ltd.
[0016] The second aspect of the present invention provides a method for preparing the semiconductor graphite material, comprising the following steps:
[0017] S1, mixing asphalt coke powder, raw petroleum coke powder, artificial graphite powder and natural graphite powder for the first time, and then adding modified asphalt for the second mixing to obtain a mixture;
[0018] S2, rolling, grinding and pressing the mixed material in sequence to obtain a blank;
[0019] S3, roasting the blank according to a predetermined temperature rise curve to obtain a roasted material;
[0020] S4. Graphitizing the calcined material to obtain a semiconductor graphite material.
[0021] In some preferred embodiments, the conditions for the first mixing in step S1 are: temperature 110-130° C., and time 60-90 min.
[0022] Preferably, the conditions for the first mixing in step S1 are: temperature 120° C., and time 80 min.
[0023] In some preferred embodiments, the conditions for the second mixing in step S2 are: first mixing with the lid closed for 80-100 minutes, and then mixing with the lid open for 3-8 minutes.
[0024] Preferably, the conditions for the second mixing in step S1 are: first mixing with the lid closed for 90 minutes, and then mixing with the lid open for 3-8 minutes.
[0025] In some preferred embodiments, the temperature of the sheet rolling in step S2 is 175-185° C., and the sheet thickness after sheet rolling is 2-4 mm.
[0026] In some preferred embodiments, the physical properties of the powder obtained after grinding in step S2 are: moisture ≤1%, volatile matter 15-20%, sieve particle size +160# ≤7%, sieve particle size -320# 45-55%.
[0027] In some preferred embodiments, the pressing method in step S2 is isostatic pressing, the pressing pressure is 130-170 MPa, and the holding time is 10-20 min.
[0028] Preferably, the pressing pressure is 150 MPa and the holding time is 15 min. Preferably, the density of the blank in step S2 is 1.3-1.8 g / cm 3 .
[0029] Preferably, the density of the blank in step S2 is 1.5±0.03 g / cm 3 .
[0030] In some preferred embodiments, the predetermined heating curve in step S3 is:
[0031] Stage 1: heating from room temperature to 320-380°C at a free heating rate;
[0032] Stage 2: heating to 400-550°C at a rate of 2-4°C / h;
[0033] Stage 3: heating to 700-920°C at a heating rate of 1-3°C / h;
[0034] Stage 4: heating to 950-1000°C at a heating rate of 3-5°C / h;
[0035] Stage 5: heating to 1100-1200°C at a heating rate of 6-10°C / h;
[0036] Stage 6: Keep at 1200℃ for 60-80h.
[0037] In some preferred implementations, the stage 2 specifically includes:
[0038] Stage 2.1: heating to 430-480°C at a heating rate of 3-3.5°C / h;
[0039] Stage 2.2: heating to 480-550°C at a rate of 2-3°C / h;
[0040] The stage 3 specifically includes:
[0041] Stage 3.1: heating to 730-770°C at a heating rate of 1-1.5°C / h;
[0042] Stage 3.2: heating to 780-820°C at a heating rate of 1.5-1.7°C / h;
[0043] Stage 3.3: Heating to 880-920°C at a heating rate of 2-3°C / h.
[0044] Preferably, the stage 2 specifically includes:
[0045] Stage 2.1: heating to 450°C at a heating rate of 3.3°C / h;
[0046] Stage 2.2: heating to 500°C at a rate of 2.5°C / h;
[0047] The stage 3 specifically includes:
[0048] Stage 3.1: heating to 750°C at a rate of 1.25°C / h;
[0049] Stage 3.2: heating to 800°C at a heating rate of 1.6°C / h;
[0050] Stage 3.3: Heating to 900°C at a heating rate of 2.5°C / h.
[0051] Most preferably, the predetermined heating curve in step S3 is:
[0052] Stage 1: heating from room temperature to 350 °C at a free heating rate of 5 h;
[0053] Stage 2.1: heating to 450°C at a heating rate of 3.3°C / h;
[0054] Stage 2.2: heating to 500°C at a rate of 2.5°C / h;
[0055] Stage 3.1: heating to 750°C at a rate of 1.25°C / h;
[0056] Stage 3.2: heating to 800°C at a heating rate of 1.6°C / h;
[0057] Stage 3.3: heating to 900°C at a heating rate of 2.5°C / h;
[0058] Stage 4: heating to 980°C at a heating rate of 4°C / h;
[0059] Stage 5: heating to 1180°C at a heating rate of 8°C / h;
[0060] Stage 6: Keep at 1200°C for 70h.
[0061] In some preferred embodiments, the conditions for the graphitization treatment in step S4 are:
[0062] (1) The calcined material is placed in a graphitization furnace, and chlorine is supplied when the furnace core temperature is 2000-2200°C, and Freon is supplied when the furnace core temperature is 2200-2400°C; or chlorine is supplied when the furnace core temperature is 2000-2200°C, and Freon and chlorine are supplied simultaneously 6 hours after the chlorine is supplied;
[0063] (2) Graphitization treatment at 2800-3000℃ for 40-50h.
[0064] Preferably, during the simultaneous delivery of Freon and chlorine, the amount of chlorine is slightly greater than the amount of Freon.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The present invention adopts specific raw materials and optimized roasting conditions, only needs to carry out one roasting treatment and graphitization treatment, does not need to carry out impregnation, the preparation method is simple and efficient, and the production cost is reduced; and the obtained semiconductor graphite material has higher flexural strength, compressive strength, hardness and density; and has lower resistivity, porosity and ash content. DETAILED DESCRIPTION
[0067] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0068] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0069] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0070] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0071] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0072] In the following examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.
[0073] The sources of raw materials involved in the embodiments and comparative examples are shown in Table 1:
[0074] Table 1
[0075]
[0076] Examples 1-3 and Comparative Examples 1-4 provide a semiconductor graphite material, the composition of which is shown in Table 2 in terms of mass percentage:
[0077] Table 2
[0078] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Asphalt coke powder 23% 28% 33% 28% 0% 39% 56% Raw petroleum coke powder 23% 28% 33% 28% 56% 15% 0% Artificial graphite powder 15% 9% 5% 14% 9% 9% 9% T395 graphite powder 8% 5% 3% 0% 5% 5% 5% Reformed asphalt 31% 30% 26% 30% 30% 32% 30%
[0079] The preparation methods of Examples 1-3 and Comparative Examples 1-4 include the following steps:
[0080] S1. Mix asphalt coke powder, raw petroleum coke powder, artificial graphite powder and natural graphite powder for the first time at a temperature of 120° C. for 80 minutes, then add modified asphalt and mix for 90 minutes with the lid closed, and then mix for 5 minutes with the lid open to obtain a mixture;
[0081] S2, rolling the mixed material into sheets: the sheet rolling temperature is 180°C, and the sheet thickness after rolling is 3mm;
[0082] Grinding: 4R grinding machine is used for grinding; the physical properties of the powder obtained after grinding are as follows: moisture: ≤1%; volatile matter: 12-18%; +160#: ≤7%; -320#: 45-55%;
[0083] Isostatic pressing: the pressure is 150MPa, the holding time is 15min, and the blank is obtained; the density of the blank is 1.5±0.03g / cm 3 ;
[0084] S3, roasting the blank according to a predetermined temperature rise curve to obtain a roasted material;
[0085] The predetermined heating curve is:
[0086] Stage 1: heating from room temperature to 350 °C at a free heating rate of 5 h;
[0087] Stage 2.1: heating to 450°C at a heating rate of 3.3°C / h;
[0088] Stage 2.2: heating to 500°C at a rate of 2.5°C / h;
[0089] Stage 3.1: heating to 750°C at a rate of 1.25°C / h;
[0090] Stage 3.2: heating to 800°C at a heating rate of 1.6°C / h;
[0091] Stage 3.3: heating to 900°C at a heating rate of 2.5°C / h;
[0092] Stage 4: heating to 980°C at a heating rate of 4°C / h;
[0093] Stage 5: heating to 1180°C at a heating rate of 8°C / h;
[0094] Stage 6: Keep at 1200℃ for 70h;
[0095] S4. Place the calcined material in a graphitization furnace. When the furnace core temperature is 2000°C, supply chlorine gas; when the furnace core temperature is 2200°C, supply Freon; and graphitize at 3000°C for 48 hours.
[0096] Comparative Example 5
[0097] The difference from Example 2 is that the predetermined heating curve in step S3 is:
[0098] Stage 1: heating from room temperature to 350°C at a free heating rate;
[0099] Stage 2: heating to 500°C at a heating rate of 3.3°C / h;
[0100] Stage 3.1: heating to 800°C at a heating rate of 1.25°C / h;
[0101] Stage 3.2: heating to 900°C at a rate of 2.5°C / h;
[0102] Stage 4: heating to 1180°C at a heating rate of 8°C / h;
[0103] Stage 5: Keep at 1200℃ for 70h.
[0104] Comparative Example 6
[0105] The difference from Example 2 is that the predetermined heating curve in step S3 is:
[0106] Stage 1: heating from room temperature to 350°C at a free heating rate;
[0107] Stage 2.1: heating to 450°C at a rate of 2.5°C / h;
[0108] Stage 2.2: Heating to 500°C at a heating rate of 3.5°C / h.
[0109] Stage 3: heating to 800°C at a heating rate of 1.25°C / h;
[0110] Stage 3.1: heating to 750°C at a rate of 2°C / h;
[0111] Stage 3.2: heating to 800°C at a heating rate of 1°C / h;
[0112] Stage 3.3: heating to 900°C at a heating rate of 3°C / h;
[0113] Stage 4: heating to 980°C at a heating rate of 6°C / h;
[0114] Stage 5: heating to 1180°C at a heating rate of 4°C / h;
[0115] Stage 6: Keep at 1200°C for 70h.
[0116] Comparative Example 7
[0117] The difference from Example 2 is that the predetermined heating curve in step S3 is:
[0118] Stage 1: heating from room temperature to 200°C at a free heating rate;
[0119] Stage 2: heating to 600°C at a heating rate of 10°C / h;
[0120] Stage 3: heating to 900°C at a heating rate of 3°C / h;
[0121] Stage 4: heating to 1000°C at a heating rate of 7°C / h;
[0122] Stage 5: heating to 1150°C at a heating rate of 15°C / h;
[0123] Stage 6: Keep at 1150°C for 50h.
[0124] The semiconductor graphite materials of Examples 1-3 and Comparative Examples 1-7 were subjected to performance tests, wherein the flexural strength test standard was JB / T 8133.7 Part 7 of the test method for physical and chemical properties of electric carbon products; the compressive strength test standard was JB / T8133.8 Part 8 of the test method for physical and chemical properties of electric carbon products; the resistivity test standard was JB / T 8133.2 Part 2 of the test method for physical and chemical properties of electric carbon products; the hardness test standard was JB / T 8133.4 Part 4 of the test method for physical and chemical properties of electric carbon products; the bulk density test standard was JB / T 8133.14 Part 14 of the test method for physical and chemical properties of electric carbon products; and the porosity test standard was JB / T 8133.15 Part 15 of the test method for physical and chemical properties of electric carbon products. The results are shown in Table 3.
[0125] Table 3
[0126]
[0127]
[0128] The semiconductor graphite material of the embodiment of the present invention has been tried out on graphite bases and clips used in semiconductor silicon wafer production by a company in my country.
[0129] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A semiconductor graphite material, characterized in that: Calculated by mass percentage, the raw materials include 23-33% of asphalt coke powder, 23-33% of raw petroleum coke powder, 5-15% of artificial graphite powder, 3-8% of natural graphite powder, and the balance is modified asphalt.
2. The semiconductor graphite material according to claim 1, characterized in that The mass ratio of the asphalt coke powder, the raw petroleum coke powder, the artificial graphite powder and the natural graphite powder is 4-7:4-7:1.6-2:
1.
3. The semiconductor graphite material according to claim 1, characterized in that The semiconductor graphite material comprises, by mass percentage, 28% asphalt coke powder, 28% raw petroleum coke powder, 9% artificial graphite powder, 5% natural graphite powder, and the remainder is modified asphalt.
4. The method for preparing the semiconductor graphite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing asphalt coke powder, raw petroleum coke powder, artificial graphite powder and natural graphite powder for the first time, and then adding modified asphalt for the second mixing to obtain a mixture; S2, rolling, grinding and pressing the mixed material in sequence to obtain a blank; S3, roasting the blank according to a predetermined temperature rise curve to obtain a roasted material; S4. Graphitizing the calcined material to obtain a semiconductor graphite material.
5. The preparation method according to claim 4, characterized in that The physical property parameters of the powder obtained after grinding in step S2 are: moisture ≤1%, volatile matter 15-20%, sieve particle size +160# ≤7%, sieve particle size -320# 45-55%.
6. The preparation method according to claim 4, characterized in that The density of the blank in step S2 is 1.3-1.8 g / cm 3 .
7. The preparation method according to claim 4, characterized in that The predetermined heating curve in step S3 is: Stage 1: heating from room temperature to 320-380°C at a free heating rate; Stage 2: heating to 400-550°C at a rate of 2-4°C / h; Stage 3: heating to 700-920°C at a heating rate of 1-3°C / h; Stage 4: heating to 950-1000°C at a heating rate of 3-5°C / h; Stage 5: heating to 1100-1200°C at a heating rate of 6-10°C / h; Stage 6: Keep at 1200℃ for 60-80h.
8. The preparation method according to claim 7, characterized in that The stage 2 specifically includes: Stage 2.1: heating to 430-480°C at a heating rate of 3-3.5°C / h; Stage 2.2: heating to 480-550°C at a rate of 2-3°C / h; The stage 3 specifically includes: Stage 3.1: heating to 730-770°C at a heating rate of 1-1.5°C / h; Stage 3.2: heating to 780-820°C at a heating rate of 1.5-1.7°C / h; Stage 3.3: Heating to 880-920°C at a heating rate of 2-3°C / h.
9. The preparation method according to claim 8, characterized in that The predetermined heating curve in step S3 is: Stage 1: heating from room temperature to 350 °C at a free heating rate of 5 h; Stage 2.1: heating to 450°C at a heating rate of 3.3°C / h; Stage 2.2: heating to 500°C at a rate of 2.5°C / h; Stage 3.1: heating to 750°C at a rate of 1.25°C / h; Stage 3.2: heating to 800°C at a heating rate of 1.6°C / h; Stage 3.3: heating to 900°C at a heating rate of 2.5°C / h; Stage 4: heating to 980°C at a heating rate of 4°C / h; Stage 5: heating to 1180°C at a heating rate of 8°C / h; Stage 6: Keep at 1200°C for 70h.
10. The preparation method according to claim 4, characterized in that The conditions for the graphitization treatment in step S4 are: (1) The calcined material is placed in a graphitization furnace, and chlorine is supplied when the furnace core temperature is 2000-2200°C, and Freon is supplied when the furnace core temperature is 2200-2400°C; or chlorine is supplied when the furnace core temperature is 2000-2200°C, and Freon and chlorine are supplied simultaneously 6 hours after the chlorine is supplied; (2) Graphitization treatment at 2800-3000℃ for 40-50h.
Citation Information
Patent Citations
Preparation method of low-resistivity isotropic graphite
CN104876581A
Preparation method of nuclear graphite material
CN107857261A
Preparation method of high-density carbon-graphite composite material
CN115353390A
Composite material, composite graphite bipolar plate, fuel cell and preparation method
CN116072905A
Preparation method of high-homogeneity special graphite material for epitaxial growth basal disc
CN117534467A
Cited By
Preparation method of refined coke powder and high-purity isostatic pressing graphite
CN120943639A
Preparation method of refined coke powder and high-purity isostatic pressing graphite
CN120943639B